PHOTOPROTECTIIVE STRATEGIES OF UNICELULAR RED ALGA RHODELLA VIOLACEA DURING ACCLIMATION TO STRONG LIGHT - Neverov , K. (EurasianUnionScientists, 2020)
Red algae contain in their photosynthetic machinery water-soluble antenna complexes - phycobilisomes (PBSs) attached to thylakoid membranes to transfer excitation energy to photosystems. Strong light absorbed by the PBSs triggers a fast formation of transthylakoid ΔpH that follows the non-photochemical quenching of chlorophyll (Chl) fluorescence. The ΔpH build-up seems to be essential for photoprotecting the photosynthetic apparatus in the absence of xanthophyll cycle common to higher plants. However, the photoprotective mechanisms of red algae are not studied in details yet. We present here our research of the Chl fluorescence quenching in unicellular red algae Rhodella violacea and its correlation with the ΔpH gradient being formed. The relation of this phenomenon to photoprotection of photosystem 2 (PS 2) in the normal and high light-acclimated Rhodella cells is also examined. Under the photoinhibitory conditions (white light of 2000-3000 μE/m2s), the ΔpH-dependent Chl fluorescence quenching was found to delay the kinetics of PS 2 photoinhibition. The uncouplers like nigericin and NH4Cl are known to break down ΔpH gradient, lead to the dissipation of Chl fluorescence quenching followed by enhancing the PS 2 photoinhibition rate. The same effect showed far-red (FR) light consuming transthylakoid ΔpH. ATPase inhibitor, DCCD, having no impact on ΔpH didn’t influence PS 2 photoinhibition as well this implies the photoprotection to be fulfilled by the proton gradient rather than by ATP synthesis. Long-term acclimation of Rhodella cells to higher irradiances (500-1000 μE/m2s) results in a partial loss of the periphery phycoerythrin-containing subunits by PBSs. The light-acclimated cultures display a higher resistance to the photoinhibitory light than the non-acclimated ones. This could be explained by diminishing the energy transfer from the reduced PBSs to PS 2 as well as light screening by the secondary carotenoids synthesized during light exposure. Data on low-temperature (77K) fluorescence allow to evaluate the molecular mechanisms of light-induced Chl fluorescence suppression in Rhodella cells and its recovery in darkness.